On the toughening mechanisms present in boron suboxide materials with sintering aids. - Bush, Peter Robert (My University, 2011)
The fracture toughness of polycrystalline boron suboxide has been substantially improved through the addition of a low amount of various sintering aids Determining the reasons behind the small amount of secondary phase increasing the toughness of boron suboxide to such an extent was the focus of this project. Fracture toughness testing was conducted on pure boron suboxide and boron suboxide containing CaO, NiO, Y2O3-Al2O3 TiB2-Y2O3-Al2O3 additions. Determining the fracture toughness through the SEVNB, IFT and COD methods, it was shown that these additives increase the toughness of boron suboxide significantly. Additionally, hardness testing of pure boron suboxide revealed a significant indentation size effect. Analysis of crack interaction with the microstructure was performed. Insufficient mechanical toughening events were observed to explain the increase in fracture toughness. Although the mechanism behind the increase in fracture toughness was not discovered, it was concluded that the sintering aids must change the surface energy of the boron suboxide matrix.